Full disclosure: Unraveling the mystery of a wide complex tachycardia - Zahrani, Mohammed (J Saudi Heart Assoc, 2017)
Wide complex tachycardia is not uncommon in patients with underlying structural heart disease and reduced ejection fraction. It is important to make the correct diagnosis as it carries prognostic and clinical implications. We present a case of a challenging wide complex rhythm detected on remote telemetry monitoring. This case outlines the differential diagnosis of a wide complex tachycardia and the clues to making a diagnosis of artifact. It highlights the importance of correct diagnosis as an incorrect diagnosis may lead to inappropriate treatments and unnecessary investigations.